A study of weather resistant dye for outdoor application [compact disc] - 344816 Loh, Poh Ping (Skudai : Universiti Teknologi Malaysia, 2006)
Project paper (Sarjana Muda Kejuruteraan (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2006